Genetic Variations in the Human Cannabinoid Receptor Gene Are Associated with Happiness - Matsunaga, Masahiro (Public Library of Science, 2014)
Happiness has been viewed as a temporary emotional state (e.g., pleasure) and a relatively stable state of being happy (subjective happiness level). As previous studies demonstrated that individuals with high subjective happiness level rated their current affective states more positively when they experience positive events, these two aspects of happiness are interrelated. According to a recent neuroimaging study, the cytosine to thymine single-nucleotide polymorphism of the human cannabinoid receptor 1 gene is associated with sensitivity to positive emotional stimuli. Thus, we hypothesized that our genetic traits, such as the human cannabinoid receptor 1 genotypes, are closely related to the two aspects of happiness. In Experiment 1, 198 healthy volunteers were used to compare the subjective happiness level between cytosine allele carriers and thymine-thymine carriers of the human cannabinoid receptor 1 gene. In Experiment 2, we used positron emission tomography with 20 healthy participants to compare the brain responses to positive emotional stimuli of cytosine allele carriers to that of thymine-thymine carriers. Compared to thymine-thymine carriers, cytosine allele carriers have a higher subjective happiness level. Regression analysis indicated that the cytosine allele is significantly associated with subjective happiness level. The positive mood after watching a positive film was significantly higher for the cytosine allele carriers compared to the thymine-thymine carriers. Positive emotion-related brain region such as the medial prefrontal cortex was significantly activated when the cytosine allele carriers watched the positive film compared to the thymine-thymine carriers. Thus, the human cannabinoid receptor 1 genotypes are closely related to two aspects of happiness. Compared to thymine-thymine carriers, the cytosine allele carriers of the human cannabinoid receptor 1 gene, who are sensitive to positive emotional stimuli, exhibited greater magnitude positive emotions when they experienced positive events and had a higher subjective happiness level.